Lactation curves for milk, fat and protein in dairy cows under regenerative versus conventional farming practices - Moreno-Gónzalez Y; López-Villalobos N; Donaghy D; López IF; MacGibbon A; Holroyd SE (Taylor and Francis Grou, 2024)
Regenerative agriculture aims to utilise more diverse pasture species and enhance animal performance through sustainable soil management and pasture quality. This study evaluated the influence of regenerative and conventional farming on dairy cow performance and milk production under different pasture mixes and management strategies. Monthly herd test records were used to model individual lactation curves for daily milk, fat, and protein yield for the 2022–2023 season using random regression with third-order orthogonal polynomials. Total yields were calculated from predicted daily yield. Treatments were SPCM: Standard pasture under conventional management, DPCM: Diverse pasture mix under conventional management, and DPRM: Diverse pasture mix under regenerative management. Total milk yield was similar across treatments, averaging 3370 kg (SPCM), 3649 kg (DPCM), and 3626 kg (DPRM) for the 2022–2023 season. No significant differences were observed in fat, protein, milk solids yield, or milk composition. Cows on diverse pastures, regardless of management approach, showed heavier liveweights than those on standard pastures. DPCM and DPRM cows averaged 474 kg, significantly greater than SPCM cows at 464 kg (P < 0.0001), likely due to longer grazing rotation and higher post-graze mass. These findings suggest that pasture species diversity, regardless the management, enhances liveweight without affecting milk composition.
Keywords: Regenerative agriculture; diverse pasture mix; dairy cow performance; milk production; lactation curves; sustainable